Tension-releasing suture appendage on single-incision sling device: A novel approach to postoperative voiding dysfunctions - Tsia-Shu Lo; Leng Boi Pue; Yiap Loong Tan; Cheng-Yu Long; Yi-Hao Lin; Pei-Ying Wu (Elsevier, 2016)
Objective: Voiding dysfunction following a midurethral sling procedure is still a relevant consequence that can affect patients' quality of life. Various invasive methods have been described to manage this problem. We hypothesize that we if we could diagnose the condition early using noninvasive tools, we would be able to offer appropriate effective management. We sought to study the effectiveness of attaching a tension-releasing suture on a single-incision sling (SIS) tape as a prophylactic measure for the treatment of immediate postoperative voiding dysfunctions, and secondarily, to evaluate the objective and subjective cure rates of the treatment for stress urinary incontinence. Materials and Methods: It is a prospective observational study. A tension-releasing suture was prepared by appending a polyglactin suture to one end of the MiniArc sling tip fiber, which could be used to manipulate the sling tip when postoperative voiding dysfunction was identified. Primary outcome measure was the number of patients requiring tension-releasing suture manipulation to treat postoperative voiding dysfunctions successfully. Results: Twelve of the 131 (9.2%) patients who underwent SIS procedure for urodynamic stress incontinence surgery required tension-releasing suture manipulation due to voiding dysfunction during the immediate postoperative period with a good outcome. Postoperative overall objective and subjective cure rates were 90.5% and 88.9% (126 available patients at 1-year follow up, mean 19.2 ± 8.0 months), respectively. The subanalysis of the objective and subjective cure rates of the group with tension-releasing suture manipulation were 91.7% (11/12) and 91.7% (11/12), and those of the group without tension-releasing suture manipulation were 90.4% (103/114) and 88.6% (101/114), respectively, at 1-year follow up. Conclusion: Tension-releasing suture is effective in the management of immediate postoperative voiding dysfunction in an SIS procedure. SIS operation has good short-term objective and subjective cure rates for female urodynamic stress incontinence.